The effect of compensation and work environment on teacher performance in private high school al hikmah medan - Chalik, Sadam; Bangun, Irwadi; Sinaga, Triana (Central Research Institute for Agriculture (CeRIA), 2024)
In the realm of education, teacher performance acts as an important component that determines the quality of education and student success. Fair compensation and an adequate work environment are key in providing motivation and productivity for teaching staff. Research has been conducted on performance and work environment at SMK AL Hikmah Medan using data collection methods in the form of questionnaires or questionnaires with the addition of data quality testing, classical assumption testing. multiple regression analysis, and hypothesis testing. Based on the results of the study, several conclusions can be drawn Compensation has a tcount> ttabel value (3.690> 2.024) and a significance value of 0.001 <0.05, it shows the results of a partial positive effect. The work environment has a tcount> ttabel value (2.727> 2.024) and a significance value of 0.010 < 0.05, it shows the results of a positive influence partially. Compensation and work environment have a value of Fhitung 8.527> Ftabel which is 3.24 with a significance of 0.00 <0.05 so it is concluded that there is a significant and positive influence between the variables of compensation and work environment simultaneously on performance at SMA Swasta Al-Hikmah medan